Welfare impact of improved maize varieties adoption and crop diversification practices among smallholder maize farmers in Ogun State, Nigeria. Issue 5 (May 2022) - Baiyegunhi, L.J.S.; Akinbosoye, F.; Bello, L.O.
Abstract: In Nigeria, the inconsistency in maize production compared to the projected average output has grave implications considering the sharp increase in maize demand and its strategic importance in addressing economic welfare issues. Thus, emphasis is placed on improved agricultural technologies for increasing farming household's productivity and income. This study explored the determinant of complementary improved maize varieties (IMVs) and crop diversification (CD) adoption on smallholder maize farmers' welfare (measured by productivity and net farm income) in Ogun State, Nigeria, using a cross sectional data obtained from a multi-staged random sampling of 200 respondents. A multinomial endogenous switching regression (MESR), that correct for endogeneity and unnoticed heterogeneity was employed to analysed the data. The results from the analysis highlighted different socioeconomic characteristics, input variables, policy, and institutional variables as the determinants of the package adoption of IMVs and CD. Estimates of the average treatment effect (ATT) from the MESR model revealed that farmers who adopt IMVs and CD in combination or in isolation realised increased maize productivity and net farm income per hectare. However, farmers who adopt only IMVs achieved the highest welfare outcomes. These findings heighten that policies that stimulate IMVs adoption should be designed, prioritised and upscale to farming areas experiencing low yields to meet farmers' socioeconomic and livelihoods conditions. Abstract : Adoption; Welfare impact; Improved maize varieties; Crop diversification; Multinomial endogenous switching regression; Nigeria.